Distribusi Kalsium (Ca) Pada Daerah Aliran Sungai Serayu - Fikriyya, Nabela; Putri, Desta Fatma; Jatmoko, Bambang Eko; Firdaus, Abdul Malik (Fakultas Perikanan dan Ilmu Kelautan, 2024)
Serayu River Watershed is one of the watersheds in Central Java that covers several districts including Wonosobo, Banjarnegara, Purbalingga, Banyumas, and Cilacap. The condition of the Serayu River Watershed at this time has experienced damage and environmental pollution which has resulted in a decrease in the quality of Serayu River Water. Calcium is one of the minerals present in water and sediment. Calcium content is influenced by reactions involving carbon dioxide gas either due to respiration of plants or aquatic animals. The presence of domestic wastewater is an external element that can affect high calcium concentrations in waters. The purpose of this study was to determine the distribution of Calcium (Ca) in the Serayu River Watershed. Sampling was conducted in November 2023 located in the Serayu Watershed Area. Sampling was carried out at 15 points of the Serayu River Watershed. The method used is titrimetric analysis. The analysis results obtained are the highest Calcium (Ca) value found in Menyawak River at 52.40 mg/L. The calcium distribution map shows a red interpolation color. The lowest Calcium (Ca) value is found in the Kalisapi River at 19.20 mg/L. The calcium distribution map shows a yellow interpolation color.